Pulsed processing by cold plasma, applied to industrial emission control - Van Heesch, E. J. M.; Huiskamp, T.; Yan, K.; Beckers, F. J. C. M.; Smulders, H. W. M.; Winands, G. J. J.; Lemmens, R. H. P.; Blom, P. P. M.; Segura, S. Davalos; Hoeben, W. F. L. M.; Van Paasen, S. V. B.; Van Oorschot, J. J.; et al. (Frontiers in Chemistry, 2024)
A promising pollution control technology is cold plasma driven chemical processing. The plasma is a pulsed electric gas discharge inside a near atmospheric-pressure-temperature reactor. The system is energized by a continuous stream of very short high-voltage pulses. The exhaust gas to be treated flows through the reactor. The methods applied involve the development of robust cold plasma systems, industrial applications and measuring technologies. Tests of the systems were performed at many industrial sites and involved control of airborne VOC (volatile organic compound) and odor. Electrical, chemical and odor measuring data were collected with state-of-the-art methods. To explain the test data an approximate solution of global reaction kinetics of pulsed plasma chemistry was developed. It involves the Lambert function and, for convenience, a simple approximation of it. The latter shows that the amount of removal, in good approximation, is a function of a single variable. This variable is electric plasma power divided by gas flow divided by input concentration. In the results sections we show that in some cases up to 99% of volatile pollution can be removed at an acceptable energy requirement. In the final sections we look into future efficiency enhancements by implementation of (sub)nanosecond pulsed plasma and solid state high-voltage technology and by integration with catalyst technology.